1999
DOI: 10.1038/10357
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gene encoding 3β- hydroxysteroid-Δ8,Δ7- isomerase cause X-linked dominant Conradi-Hünermann syndrome

Abstract: X-linked dominant Conradi-Hünermann syndrome (CDPX2; MIM 302960) is one of a group of disorders with aberrant punctate calcification in cartilage, or chondrodysplasia punctata (CDP). This is most prominent around the vertebral column, pelvis and long bones in CPDX2. Additionally, CDPX2 patients may have asymmetric rhizomesomelia, sectorial cataracts, patchy alopecia, ichthyosis and atrophoderma. The phenotype in CDPX2 females ranges from stillborn to mildly affected individuals identified in adulthood. CDPX2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
244
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(254 citation statements)
references
References 26 publications
10
244
0
Order By: Relevance
“…Diseases that are classically regarded as ichthyosis in the previously published scientific literature and that will continue to be included are shown in Figs 4 and 5. They include Sjögren-Larsson syndrome 75,76 ( Fig 5, B), Refsum syndrome, 77,78 neutral lipid storage disease with ichthyosis (also referred to as ChanarinDorfman syndrome) (Fig 5, G), 40,79,80 ichthyosis folliculariseatrichiaephotophobia syndrome (Fig 5, D), 81,82 Conradi-Hünermann-Happle syndrome (CDPX2) (Fig 5, F ), 83,84 multiple sulfatase deficiency, 85,86 congenital reticular ichthyosiform erythroderma also referred to as ichthyosis variegata 87 (or ichthyosis en confettis 88 ) (Fig 4, E ), and ichthyosis prematurity syndrome 89,90 (Fig 5, E ). In ichthyosis prematurity syndrome, affected pregnancies exhibit abnormal amniotic fluid both on ultrasound imaging and clinically.…”
Section: Other Diseases Considered In the Classification Of Inheritedmentioning
confidence: 99%
See 1 more Smart Citation
“…Diseases that are classically regarded as ichthyosis in the previously published scientific literature and that will continue to be included are shown in Figs 4 and 5. They include Sjögren-Larsson syndrome 75,76 ( Fig 5, B), Refsum syndrome, 77,78 neutral lipid storage disease with ichthyosis (also referred to as ChanarinDorfman syndrome) (Fig 5, G), 40,79,80 ichthyosis folliculariseatrichiaephotophobia syndrome (Fig 5, D), 81,82 Conradi-Hünermann-Happle syndrome (CDPX2) (Fig 5, F ), 83,84 multiple sulfatase deficiency, 85,86 congenital reticular ichthyosiform erythroderma also referred to as ichthyosis variegata 87 (or ichthyosis en confettis 88 ) (Fig 4, E ), and ichthyosis prematurity syndrome 89,90 (Fig 5, E ). In ichthyosis prematurity syndrome, affected pregnancies exhibit abnormal amniotic fluid both on ultrasound imaging and clinically.…”
Section: Other Diseases Considered In the Classification Of Inheritedmentioning
confidence: 99%
“…Conradi-Hünermann-Happle (CDPX2) and CHILD syndrome are both caused by an enzyme defect within the distal cholesterol biosynthetic pathway as a result of X-linked dominant mutations in the EBP (CDPX2) and NSDHL (CHILD) genes, respectively. 84,146 However, CDPX2 may present with severe CIE or collodion membrane and is therefore regarded as an ichthyosis (Fig 4, F ). 147 Darier disease 148,149 and HaileyeHailey disease 150 are autosomal dominant genodermatoses 151,152 The typical lesions of Darier diseaseeusually beginning in adolescenceeare tiny keratotic papules with a firmly adherent keratin cap, and are most often found on the seborrheic areas, scalp, and extremities; generalized involvement is very rare.…”
Section: Other Diseases Considered In the Classification Of Inheritedmentioning
confidence: 99%
“…As they move towards the upper layers, the keratinocytes become flatter and produce a mixture of lipids, cholesterol, free saturated fatty acids and ceramides into the intercellular spaces and thereby contributes to making the epidermis an effective barrier. Decreased cholesterol content in the stratum corneum could be attributable to the barrier function abnormality (Elias et al, 2008;Williams and Elias, 1981 (Klar et al, 2009) , lamellar ichthyosis (Lefevre et al, 2003) , harlequin ichthyosis (Kelsell et al, 2005), Conradi-Hünermann-Happle syndrome, (Braverman et al, 1999), CHILD syndrome (Konig et al, 2000) and X-linked Ichthyosis (Basler et al, 1992), to which MBTPS2 is now added, causing both IFAP and KFSD.…”
Section: Nonsyndromic) Kfsdmentioning
confidence: 99%
“…In addition to its role in sterol isomerization, SI also functions as a multidrug-binding protein for various drugs, including the Ca 2ϩ antagonist emopamil, the immunosuppressant SR31747A, and the antiestrogen tamoxifen (12)(13)(14)(15). Furthermore, recent genetic analyses revealed that mutations in the SI gene cause X-linked dominant Conradi-Hü nermann syndrome in humans and Tattered in mice, which is one of the disorders with aberrant punctate calcification in cartilage or chondrodysplasia punctata (16,17). Clinical and biochemical data on the Conradi-Hü nermann syndrome patients show an accumulation of 8(9)-cholesterol and 8-dehydrocholesterol in plasma because of a defect at C8-C7 (8-ene-7-ene) isomerization.…”
Section: Srebpsmentioning
confidence: 99%